FROM BUREAUCRATIC RED TAPE TO DIGITAL GOVERNANCE: EVALUATING PUBLIC SERVICE TRANSFORMATION IN INDONESIA - Sarjito, Aris (Decision, 2025)
Digital governance has emerged as a crucial element in modern public administration, aiming to enhance efficiency, transparency, and accessibility in government services. Indonesia has implemented various e-Government initiatives, yet challenges persist, including inadequate infrastructure, cybersecurity threats, digital illiteracy, and bureaucratic resistance. This study explores policy recommendations to optimize digital governance in Indonesia by addressing these barriers. A qualitative approach was used, analysing academic literature, case studies, and policy frameworks related to digital transformation. The results indicate that expanding broadband access, strengthening cybersecurity measures, promoting digital literacy, and streamlining bureaucratic processes are critical for improving e-Government effectiveness. Additionally, integrating interoperable digital systems and enhancing public participation through open data initiatives can further strengthen governance. The study concludes that a comprehensive policy framework combining technological investments, regulatory improvements, and human capital development is essential to achieving a more effective and inclusive digital governance ecosystem in Indonesia.